Taking away the Cambodia water festival - SONG, Dabin (KDI School, 2023)
This paper examines the effect of the cancellation of the Cambodia Water Festival on household income and expenditure, using data from the Cambodia Socio-Economic Survey from 2009 to 2019. Following the tragic stampede at the 2010 Water Festival in Phnom Penh, the Festival was canceled for four years. Using this natural experiment, this paper addresses the question of how the cancellation of the Water Festival affects household income and expenditure in Cambodia. This study discovers that the cancellation of the Water Festival led to increases in total household income by 10.7% to 12.3% and total expenditure by 4.6% to 6.3%. This increase is primarily driven by households outside Phnom Penh, those with lower incomes, or those headed by males. These findings suggest that the lack of festivals and holidays contributes to Cambodia’s economic revitalization. This paper has implications for policymakers seeking a trade-off between holidays and labor productivity, and it provides insights into the optimal level of holidays.
Thesis(Master) -- KDI School: Master of Devemopment Policy, 2023
Keywords: Income distribution--Cambodia; Economic development--Cambodia